Uji Evektivitas Larutan Pembersih Kerak Falling Film Plate Evaporator di Pabrik Gula Sulfitasi - Risvan Kuswurjanto (Seminar Nasional Teknik Kimia Kejuangan, 2017)
In an effort to improve energy efficiency of the evaporator station, Falling Film Plate Evaporator (FFPE)can be used as solution. Though it indicated an improved performance of evaporator station there has been aserious problems of hard scales formation. Chemical cleaning with commercial formula wasn’t effectiveenough to remove scale at normal operation period. As interim effort the problems is approach by shorteningoperation cycle of FFPE to 8-10 days to prevent thicker scale formation. Therefore research is needed tolook for an effectives and friendly formula for FFPE scales cleaning. The preliminary results showedthat FFPE scale with working cycle of 8-10 days was thin, less than 1 mm thickness and weight of 2.89mg/cm2. The scale has a soft texture, a bit fragile and blackist brown colour. The KA and KB (Kom - 2)combination was more effective than single one (Kom - 1). The factory trial shows that the performanceof FFPE was better after cleaning than before. After acid cleaning and washing the bottom of plate pack wascleaner.